Modelling study of stress displacement theories for retaining walls under seismic excitation - Su, Yang (Curtin University, 2014)
A strutted retaining wall system under seismic excitation was modeled by PLAXIS and ABAQUS. The results were evaluated based on analytical theories based on stress displacement behavior. The results showed good general agreement between modeling and theoretical results. A method is produced to utilize numerical output to gain relevant theoretical parameters. The variance in local wall response was critically studied and a new direction was proposed for seismic stress displacement behavior of retaining walls.